EFFICACY AND SAFETY OF TRIAMCINOLONE ACETONIDE INJECTION IN SUPRACHOROIDAL SPACE IN SUBJECTS WITH DIABETIC MACULAR EDEMA - FATIMA, M; ABBAS, S; SAJJAD, T (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to assess the effectiveness and safety of triamcinolone acetonide administered through suprachoroidal space in subjects with diabetic macular edema. A prospective study was conducted in the Department of Ophthalmology, Nishtar Hospital, Multan, from April 2022- April 2023. A total of 40 patients with diabetic macular edema by optical coherence tomography were included in the study. During surgery, 4mg/100 µL triamcinolone acetonide was injected. The patients were followed up for a week to evaluate post-injection adverse effects. In addition, It was noted that the injection improved the VA significantly. After 6 months of follow-up, the VA was 0.69 ± 0.1 (p<0.001). Significant improvement was seen in optical coherence tomography measurement; after 6 months, it was reduced to 265.6 ± 39.1 µm (p<0.001). No significant difference was noted in intraocular pressure from baseline to follow-up. Based on the results, administering triamcinolone acetonide through suprachoroidal space in diabetic macular edema is effective without any adverse effects.